DEVELOPING COPY THE MASTER METHOD DURING THE MONTH OF WRITINGIN THE LANGUAGE CORNER AS A METHOD OF ATTRACTIVE SOCIALIZATIONTO IMPROVE THE WRITING ATMOSPHERE IN THE FACULTY OF LANGUAGES ANDARTS OF YOGYAKARTA STATE UNIVERSITY - Sri Ayu H; Puspita Melati; Gisela Aventia B.; Sri Handayani; Siti Nasibah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The purposes of this research were to reveal the application of Copy the MasterMethod during the Month of Writing in the Language Corner (MWLC) event to improvethe atmosphere of scientific writing in the Faculty of Languages and Arts and tofind out the influence of MWLC event to the atmosphere of scientific writing in thisfaculty .This research used surveys, observations, and questionnaires to collect data.The technique of data analysis was a descriptive analysis. The research procedureconsisted of conducting observation and data collection, planning for data recording,examining instruments, and evaluation.The results of this research were the development and application of Copy theMaster Method on MWLC events such as Socialization of Student Creativity Programsand their stands, and a presentation competition. In addition, MWLC influenced thescientific writing in the Faculty of Languages and Arts. 64% students said that MWLCwas an interesting and attractive program to socialize Student Creativity Programs,and after MWLC event was held, 69% students said that they were interested inwriting for the programs.